“Oh, No, That Is Too Controversial!” Pre-service Teachers’ Perceptions of Controversial Issues: A Case Study - Shouqing Si (Universal Journal of Educational Research, 2025)
Classroom discussion and deliberation of controversial public and social issues greatly contribute to democratic education; however, pre-service teachers in social studies have been poorly prepared in teaching in this area. This qualitative case study collects multiple sources of data (i.e., interviews, self-reflection, and observation) from 13 participants and autoethnography, exploring pre-service elementary social studies teachers’ perceptions of deliberating controversial issues. Two research questions are targeted: 1) What is pre-service teachers’ rationale for teaching controversial issues? 2) What issues are considered controversial by pre-service social studies teachers in the classroom? Constant comparative data analysis reveals that inconsistency and confusion over defining controversy prevails while everyone holds a sound rationale for teaching controversial issues. A number of controversial issues are reported. Teacher educators must continue to devote efforts to developing student teachers’ content and pedagogical knowledge and skills in incorporating controversies in the K-12 classroom. The goal of incorporating controversies is not to avoid discomfort, but to guide young citizens through it with integrity and poise.